The Great Recession and Import Protection : The Role of Temporary Trade Barriers - Bown, Chad P. (London: Centre for Economic Policy Research and the World Bank, 2013)
The great recession of 2008-9 caused a negative shock to the global economy that is comparable with the great depression of the 1930s. The major advanced nations experienced painful economic contraction, severe dislocation to industrial production and sharp spikes in unemployment. Trade flows collapsed across all the regions of the world. The rest of this introductory chapter proceeds as follows. Next, the report provide a more detailed timeline and summary of events in the great recession, including its macroeconomic and trade impacts, the uncertainty over trade policy in 2008-9, and the response to calls for additional monitoring of trade policy. In particular, section one highlight the real time monitoring efforts of the World Bank's global antidumping database and subsequent temporary trade barriers (TTBs) database. These contributions have addressed some of the immediate concern about the unknown scale of protectionism taking place in 2008-9, but they have also revealed a lack of informational preparedness that has ultimately spurred this volume's research. In section two, the author introduce a relatively simple methodological framework to improve intertemporal assessment of the scope of TTB use, an approach that many of the volume's chapters adopt or modify to construct better measures of the 'stock' and 'flow' of imported products that countries subject to TTBs. (A more technical description of the methodology is provided in the Appendix (section six), along with details of the many common data sources used across the subsequent chapters.) What are the empirical results? Section three provides a simple application of this methodology and finds that, during the crisis, these economies collectively increased by 25 percent the imported products that they subjected to TTB import protection. Nevertheless, it turns out this collective expansion in TTB coverage during 2008-9 was dominated by emerging economies. Developing countries used TTBs to cover 39 percent more imported products by the end of 2009 compared with 2007, whereas recession-ravaged high-income economies surprisingly increased their coverage by only 4 percent. However, it is also clear from the data that understanding these crisis changes demands recognition of longer term trends. Thus, given these high-level results, Section 4 turns to a number of common questions that the subsequent chapters investigate, on an economy-by-economy basis, in more detail. This section provides a short preview of how the volume's authors subsequently address these questions by placing the trade policy changes of 2008-9 into historical context. Section five then concludes.